2019
DOI: 10.1002/jsde.12354
|View full text |Cite
|
Sign up to set email alerts
|

Drag Reduction by Wormlike Micelles of a Biodegradable and Non‐Biodegradable Surfactants

Abstract: This study describes the effects of wormlike micelles formed by the commercial surfactants tallowalkylamidopropyl dimethylamine oxide (Aromox APA‐TW) and oleyl methyl bis(2‐hydroxyethyl) ammonium chloride (Ethoquad O/12) as drag reducers. Ethoquad O/12 is immune to degradation by heat and microorganisms. Conversely, Aromox APA‐TW is biodegradable in the environment, and its susceptibility to heat‐induced degradation was previously assessed. This work considers the effects of temperature, salt, and time on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The study has shown that the VES-based fluids produce less surface tension than borate-cross-linked gel . In addition, friction reduction due to the VES gel is a known phenomenon, , and VES’s use as the FR is a topic of interest to researchers. , The principle of reducing friction in the surfactant systems is similar to that of high-molecular-weight polymers. The elongated wormlike micelles intertwine with each other, forming a highly viscoelastic fluid, similar to a polymer solution.…”
Section: Application Advantages For Ves Fracturing Fluidsmentioning
confidence: 99%
“…The study has shown that the VES-based fluids produce less surface tension than borate-cross-linked gel . In addition, friction reduction due to the VES gel is a known phenomenon, , and VES’s use as the FR is a topic of interest to researchers. , The principle of reducing friction in the surfactant systems is similar to that of high-molecular-weight polymers. The elongated wormlike micelles intertwine with each other, forming a highly viscoelastic fluid, similar to a polymer solution.…”
Section: Application Advantages For Ves Fracturing Fluidsmentioning
confidence: 99%
“…After the surfactant is subjected to strong shear, the colloidal structure in the solution will also be dissociated and destroyed, but after the strong shear force disappears, the colloidal structure will be regenerated automatically in a second, that is, it has the function of self-repair. 64 Therefore, in the actual liquid circulation system with pumps, the surfactant is more suitable to achieve the purpose of reducing friction drag and saving power consumption of driving pumps for a long time. Similar to polymers, the DR ability of surfactants increases gradually with the increase in concentration until it reaches the highest level of DR.…”
Section: Polymer Drag Reductionmentioning
confidence: 99%
“…These morphologies can also be manipulated by the addition of cosurfactants, counterions, and electrolytes to form particularly interesting and exotic architectures such as wormlike micelles (WLMs), disk-like micelles, , or even hamburger-like micelles . Of particular interest are WLMs, which underpin the formulation of many complex fluids, from personal care products such as shampoos, through to fracturing fluids, , drag reduction agents, and viscosity modifiers . More recently, stimulus responsiveness has been targeted in order to modulate WLM rheology in the presence of light, CO 2 , or changes in pH. Depending on the specific surfactants used and their concentrations, WLMs typically have very large aspect ratios, with diameters of only a few nanometers and lengths of several micrometers, allowing for polymer-like complex fluid behaviors above the micelle overlap concentration C *, most notable of which is viscoelasticity.…”
Section: Introductionmentioning
confidence: 99%
“…These morphologies can also be manipulated by the addition of cosurfactants, counterions, and electrolytes to form particularly interesting and exotic architectures such as wormlike micelles (WLMs), 1−3 disk-like micelles, 4,5 or even hamburger-like micelles. 6 Of particular interest are WLMs, which underpin the formulation of many complex fluids, from personal care products such as shampoos, 7 through to fracturing fluids, 8,9 drag reduction agents, 10 and viscosity modifiers. 11 More recently, stimulus responsiveness has been targeted in order to modulate WLM rheology in the presence of light, CO 2 , or changes in pH.…”
Section: ■ Introductionmentioning
confidence: 99%